Effect of paper or silver nanowires-loaded paper interleaves on the electrical conductivity and interlaminar fracture toughness of composites - Guo, Miaocai; Yi, Xiaosu (MDPI, 2018)
The effect of plant-fiber paper or silver nanowires-loaded paper interleaves on the electrical conductivity and interlaminar fracture toughness of composites was studied. Highly conductive paper was prepared by surface-loaded silver nanowires. The percolation threshold appeared at about 0.4 g/m2. The surface resistivity reached 2.3 Ω/sq when the areal density of silver nanowires was 0.95 g/m2. After interleaving the conductive papers in the composite interlayers, in-plane electrical conductivity perpendicular to the fiber direction was increased by 171 times and conductivity through thickness direction was increased by 2.81 times. However, Mode I and Mode II interlaminar fracture toughness decreased by 67.3% and 66.9%, respectively. Microscopic analysis showed that the improvement of conductivity was attributable to the formation of an electrical conducting network of silver nanowires which played a role in electrical connection of carbon fiber plies and the interleaving layers. However, the density of the highly packed flat plant fibers impeded the infiltration of resin. The parallel distribution of flat fibers to the carbon plies, and poor resin-fiber interface made the interlaminar fracture occur mainly at the interface of plant fibers and resin inside the interleaves, resulting in a decline of the interlaminar fracture toughness. The surface-loading of silver nanowires further impeded the infiltration of resin in the densely packed plant fibers, resulting in further decline of the fracture toughness